Features of Creation of Degrees of Comparison Individual and Authorial Adjective in Ukrainian Poetic texts XX-XXI Centuries (Linguostylistic Studies, 2019)
The theoretical bases of the deviant formation of the degrees of comparison of individuall and authorial adjectives the Ukrainian poetry of the XX–ХХI age as the effective way of creating estimation meaning are considered. Are described in modern linguistics views on grammatical status, volume, paradigm of category of degrees of comparison, and also amount of gramem of this category, differences between them.From artistic works the Ukrainian poets of analysable period are selected basic morpheme types of the use of forms of degrees of comparison of adjectives for expression of evaluation values. As a result of analysis of the resulted examples a conclusion is done, that similar morphological word-formation processes are the deviant formation, which despite morphological norms unite in gradation rows.It is resulted individuall and authorial adjectives which can have for it a word-formation base not attributive, but substantivni, initial units, and elementary formal relations, mediated an intermediate (virtual, imaginary) element, demonstrate relatively. Key words: individual and authorial adjective, category of degrees of comparison, norm, feature, Ukrainian poetry of XX–ХХI age. References